SANAL FİZİK TEDAVİ PLATFORMU - ÖZTÜRK, EVREN (Fırat Üniveristesi, 2017)
Günümüz koşulları göz önünde bulundurulduğunda insanlar genel olarak ev, iş ve okul döngüsünde yaşamaktadır. Bireylerin son zamanlarda dijital oyunlara ve iletişim araçlarına olan bağımlılıklarının artması ile birlikte sosyal aktivitelerinde de azalmalar görülmektedir. Bunun bir sonucu olarak nörolojik, ortopedik, romatizmal vb. birçok sağlık sorununu da bireyler yaşamaktadırlar. Teknolojinin gelişimi ile birlikte birçok alanda olduğu gibi fizyoterapi ve rehabilitasyon alanında da sağlığı koruma amaçlı teknoloji temelli rehabilitasyon yöntemleri uygulanmaktadır. Teknoloji temelli rehabilitasyon ile bireylerin fiziksel aktivitelerini geliştirmesi sağlanabilmektedir. Aynı zamanda bireylerde dengeyi artırmak, kaslardaki kuvveti geliştirmek, sağlığı koruma gibi amaçlarla da teknoloji temelli uygulamalardan faydalanabilmektedir. Kinect, rehabilitasyon alanında günümüzde ilgi gören bir teknolojidir. Bu çalışmada gerçek zamanlı 3B algılama sistemlerinden Kinect teknolojileri kullanılarak bireylere fizik tedavi hareketleri yapabilmesini sağlayan bir tedavi ve eğitim amaçlı bir platform oluşturulmuştur. Bireyin yapacağı egzersiz hareketleri Eğitmen tarafından bireye öğretilmektedir. Bireyin bu egzersiz hareketlerini doğru ve eksiksiz bir şekilde yapıp yapmadığının kontrolü yapılmaktadır ve egzersiz sonrası bireyin hareketleri başarabilme oranı ile ilgili istatistiki bilgiler sunulmaktadır. Egzersiz hareketlerinin tamamlanması sonrasındaki verilen istatistiki bilgiler ve bu bilgilerin e-posta yolu ile Fizik Tedavi Uzmanı' na gönderilmesi Fizik Tedavi Uzmanı' nın hastası hakkında anlık olarak bilgilendirilmesine imkân vermektedir. Yapılan çalışma ile Fizik Tedavi Uzmanlarının hastalarının durumunu takip edebilmeleri kolaylaştırılarak muayene sürelerinin de kısalmasına katkıda bulunmaktayız.

If we consider today's conditions, people generally live in home, work and school cycle. Along with the increasing dependence of individuals on digital gaming and communication tools in recent times, there has also been a decrease in social activities. As a result, individuals; Neurological, orthopedic, rheumatic and many other health problems are also living As with the development of technology there are many field of physiotherapy and rehabilitation of as well as technology-based rehabilitation methods for the protection of health are applied. With technology-based rehabilitation, it is possible to develop individual physical activities. At the same time, it can benefit from technology-based practices with the aim of increasing the balance of individuals, improving the strength of their muscles, and protecting their health. Kinect is a technology that is attracting attention today in the field of rehabilitation. In this study, using the Kinect technologies which is one of the real-time 3D detection systems, a platform has been established for treatment and education that enables individuals to make physical therapy movements. The exercises that will be done by the individual are taught by the instructor. The exercises of the individuals are controlled whether they are done accurate or not and also statistical information about the rate of the accuracy of these exercises is presented. The information of the statistics that are given after the completion of the exercises and sending this information via e-mail to the Physical Therapy Specialist provides the Physical Therapy Specialist to be informed about his patient. With this study, we are helping to make physical therapies by drawing attention to the idea that individuals are playing a game. We make it easier for Physical Therapy Specialists to follow the situation of their patients and help to shorten examination times. In this way, we are also introducing an innovation in the field of health and physical therapy as it is possible to treat more individuals.
The development of a virtual physical therapy environment by using microsoft kinect
Keywords: Bilgisayar Mühendisliği Bilimleri-Bilgisayar ve Kontrol